Implementation of Quality Management System Performance by Batching Plant Service Provider in Kabupaten Aceh Besar - Chandra Nst, Hartawan; Oktaviani, Cut Zukhrina; Bulba, Alfa Taras (Riviera Publishing, 2022)
Introduction: Ready-mix concrete service providers from batching plants in Aceh Besar District include PT. A, PT. B, PT. C, and PT. D. The production service provider, even though it has ISO 9001:2015 certification, is not consistent with the quality of the product. This study aims to determine the performance of the quality management system implemented by a batching plant production service provider in Aceh Besar District. The production quality of the batching plant under review is the standard deviation of the compressive strength of the concrete on the Sigli – Banda Aceh Toll Road Project. Methods: This study uses a quantitative method approach through a questionnaire. The population is addressed to the personnel of PT. Adhi Karya (Persero) Tbk, which deals with batching plant production, namely project production manager, supervisor, and quality control. Respondents addressed the personnel of PT. Adhi Karya (Persero) Tbk is a service user related to batching plant production, namely project production manager, supervisor, and quality control. Results: The results showed that the performance of the quality management system needs to be improved on a high-priority scale for PT. A is the organizational context for PT. B is the organizational and planning context, and for PT. D is planning. Conclusion: Performance of PT. What needs to be maintained is planning, operations, leadership, and support; what needs to be improved on a low priority scale is performance improvement and evaluation, and what needs to be improved on a high priority scale is the organizational context